1984
DOI: 10.1038/312643a0
|View full text |Cite
|
Sign up to set email alerts
|

Production of functional chimaeric mouse/human antibody

Abstract: The availability of monoclonal antibodies has revived interest in immunotherapy. The ability to influence an individual's immune state by administering immunoglobulin of the appropriate specificity may provide a powerful approach to disease control and prevention. Compared with immunoglobulin from other species, human immunoglobulin (Ig) might be best for such therapeutic intervention; it might function better with the recipient's effector cells and should itself be less immunogenic. The success of the mouse h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
176
0
6

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(185 citation statements)
references
References 23 publications
3
176
0
6
Order By: Relevance
“…Even at this early stage in development, the science revealed the challenge of maintaining tolerance to such therapeutic antibodies. Chimeric antibodies were developed to meet this challenge by fusing mouse variable domain regions to human constant regions [7]. By the early 1990s, the stage was set with the emerging understanding of TNFa in inflammatory diseases and the technology to target this protein with chimeric antibodies.…”
Section: Development Of Infliximabmentioning
confidence: 99%
“…Even at this early stage in development, the science revealed the challenge of maintaining tolerance to such therapeutic antibodies. Chimeric antibodies were developed to meet this challenge by fusing mouse variable domain regions to human constant regions [7]. By the early 1990s, the stage was set with the emerging understanding of TNFa in inflammatory diseases and the technology to target this protein with chimeric antibodies.…”
Section: Development Of Infliximabmentioning
confidence: 99%
“…Variable (V) regions bind antigens (Ag) and constant (C) parts bear effector functions Correspondence address: Y. Kurosawa, Institute for Comprehensive Medical Science, Fujita-Gakuen Health University, Toyoake, Aichi 470-l 1, Japan Abbreviations: Ab, antibody; Ag, antigen; C, constant; D, diversity; ELISA, enzyme-linked immunosorbent assay; H, heavy; Ig, immunoglobulin; J, joining; L, light; PAB, pazobenzenarsonate; PAGE, polyacrylamide gel electrophoresis; PBS, phosphate-buffered saline; PC, phosphorylcholine; V, variable such as binding and activation of complements, stimulation of phagocytosis by macrophages, and triggering of granule release by mast cells. Utilizing the dual characters in the structure of Ab, two research groups [3,4] succeeded in constructing chimeric molecules consisting of mouse-derived V regions and human-derived C regions. These chimeric Ab retained specificity for the haptens phosphorylcholine (PC) [3] and trinitrophenyl [4].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the dual characters in the structure of Ab, two research groups [3,4] succeeded in constructing chimeric molecules consisting of mouse-derived V regions and human-derived C regions. These chimeric Ab retained specificity for the haptens phosphorylcholine (PC) [3] and trinitrophenyl [4]. Since these studies several groups have reported production of similar chimeric Ab showing antitumor activities [5-l 11.…”
Section: Introductionmentioning
confidence: 99%
“…However, human anti-mouse antibody (HAMA) was detected in all of the patients who received A7-NCS (Spiegelberg and Weigle, 1965). The latest approach has been the production of human/mouse chimeric antibodies composed of the antigen-binding variable region from a murine MAb and the constant region of a human immunoglobulin (Morrison et al, 1984;Boulianne et al, 1984). Since the constant region of the mouse/human chimeric antibody is human, HAMA production should be decreased.…”
mentioning
confidence: 99%